Profiling the mental characteristics of sub-elite marathon runners - Coumbe-Lilley, J. E.; Hamstra-Wright, K. L.; Weidner, A. (The Sport Journal, 2015)
There has been considerable increase in the number of participants running marathons between 1990 and 2014 with the majority of runners between 23-54 years of age (Running USA, 2015). With the increase in the number of people and the range of abilities running marathons, it is important to the field of sport psychology to understand the preparatory, performance, and recovery needs of this group of athletes. The primary purpose of our institutional review board approved study was to describe the psychological skills profile of sub-elite marathon competitors to understand the important mental qualities leading runners to complete a marathon. The secondary purpose was to draw conclusions for future applied sport psychology intervention research. Healthy adults participating in an 18-week marathon training program were recruited for the study (N=125; 30M, 95F; 20-70 years of age). Participants received electronic surveys at four time points corresponding with the training program: pre-training, 6 weeks, 12 weeks, and post-training. Participants completed the nine mental skills survey (9MS) (Lesyk, 1998). The 9MS uses 30 items, rated 1-10 with three subscales: Basic (attitude; motivation; goals and commitment; people skills), Preparatory (self-talk; mental imagery), and Performance (dealing with anxiety; dealing with emotions; concentration). After exclusion of incomplete surveys, 43 (9M, 34F) surveys were analyzed. An analysis of the mean response for the 9MS subscales across each training time point was conducted via t-tests (p<0.05) The results of the analysis demonstrated attitude and goals commitment strengthened from week 6 to week 12. Perceived ability to cope with anxiety and manage emotions decreased from pre-training through post-training. Motivation, self-talk, and imagery were inconsistently rated over time.